PERBUATAN PIDANA YANG DILAKUKAN OLEH PENGEDAR NARKOTIKA DENGAN MENGGUNAKAN TEKNOLOGI INTERNET DAN APLIKASI VPN - Hendro Utaryo (universitas islam darul ulum lamongan, 2019)
The growing population and the development of communication technology led to the increasing use of Internet technology. Narcotics circulation through the development of Internet technology and VPN applications is the impact of misuse of the positive functions of a technology that has evolved into negative functions and against the law. The use of technology that has evolved from a communication device by the narcotics distributor to market their narcotics trading quickly, briefly, and veiled with the intent of activities that will be disseminating and trading narcotics not May be known by the authorities. This research uses normative research method by analyzing about criminal action conducted by narcotics distributor using Internet based technology and VPN application as well as determining locus delicti from The cause of the cyberlaw and its accountability for narcotics dealers.